Investment valuation and appraisal / Nor Nazihah Chuweni ... [et al.] - Chuweni, Nor Nazihah; Abdullah, Lizawati; Che Pin, Siti Fairuz; Johaimi Ling, Nur Lesya Firsya; Mohd Fawzy, Faza Fayza
Our motivation for writing this book is our undergraduate students. After teaching real estate valuation courses for the previous few years, students eagerly looking forward to having a module that could be used to truly comprehend the basic knowledge of real estate investment valuation and appraisal. There is a need in the market for a module that attempt to fill the gap between academic and practical paradigm. Understanding that real estate is not all mathematical, this book provide adequate text for undergraduate and investors to familiarise themselves with investment theory and other material in this module. This is mainly because, making real estate investment decision depends on being able to obtain useful information and to apply investment theories. Therefore, this material is also relevant to investors who want to better understand how to evaluate the return or yield for an investment both in traditional or non-traditional approaches. This book aims to provide a better understanding on real estate investment particularly in the aspect of investment processes, valuations and appraisals. Chapter 1 develops the understanding of the reader on the overview of investment before focusing on the property as an investment in Chapter 2. The latter chapters describe the valuations and appraisals of freehold and leasehold interests. These include the landlord-tenant valuations of marriage values, premiums and discounted cash flows.